Semiquantitative Culture Analysis during Therapy for Mycobacterium avium Complex Lung Disease - Griffith, David E. (Am J Respir Crit Care Med, 2015)
Rationale: Microbiologically based criteria such as sputum culture conversion to negative have traditionally been used to define treatment success for mycobacterial diseases. There are, however, limited data regarding whether nontuberculous mycobacterial sputum culture conversion or semiquantitative culture analysis correlates with subjective or nonmicrobiologic objective indices of treatment response. Objectives: To determine whether a semiquantitative mycobacterial culture scale correlated with clinical disease status and was predictive of long-term sputum mycobacterial culture conversion to negative in a cohort of patients with nodular/bronchiectatic Mycobacterium avium complex lung disease undergoing therapy. Methods: One hundred and eighty patients undergoing standard macrolide-based therapy for M. avium complex lung disease were monitored at standard frequent intervals with symptomatic, radiographic, and microbiologic data collected, including semiquantitative mycobacterial culture analysis. Analyses were used to evaluate clinical and microbiologic predictors of long-term sputum conversion to culture negative. Measurements and Main Results: After 12 months of therapy, 148 (82%) patients had sputum conversion to culture negative. Baseline semiquantitative sputum culture scores did not differ between patients with sputum conversion and those without. The change in sputum culture semiquantitative score from baseline to Month 3 was highly predictive of subsequent sputum long-term conversion status indicative of treatment success, as was improvement in cough, and especially early radiographic improvement. Conclusions: Early semiquantitative sputum agar plate culture results can be used to predict symptomatic and radiographic improvement as well as long-term sputum culture conversion to negative in this population. We suggest that semiquantitative sputum culture scores can be a useful tool for evaluating new nontuberculous mycobacterial lung disease therapies.